Undernutrition is feeding the tuberculosis pandemic: A perspective. (May 2022) - Carwile, Madeline E.; Hochberg, Natasha S.; Sinha, Pranay
Abstract: Tuberculosis (TB) is a major cause of death worldwide, with 1.5 million deaths in 2020. While TB incidence and mortality had previously been on a downwards trend, in 2020, TB mortality actually rose for the first time in a decade, largely due to the COVID-19 pandemic. Undernutrition is the leading risk factor for TB, with a population attributable fraction (PAF) of 15%, compared to 7.6% for HIV. Individuals who are undernourished are more likely to develop active TB compared to those with a healthy bodyweight. They are also more likely to have greater severity of TB, and less likely to have successful TB treatment outcomes. The likelihood of TB mortality significantly increases as weight decreases. Nutritional interventions are likely to improve both nutritional status and TB treatment success, thereby decreasing TB mortality. However, many previous studies focusing on nutritional interventions have provided insufficient calories or been underpowered. Nutritional supplementation will be particularly important as factors such as the COVID-19 pandemic, climate change, and political conflict further threaten food security. The global TB elimination effort can no longer afford to ignore undernutrition.